The Analisis Keterampilan Berpikir Kreatif Peserta Didik Kelas XI Fase F Bio F SMAN 2 Padang: Analisis Keterampilan Berpikir Kreatif Peserta Didik Kelas XI Fase F Bio F SMAN 2 Padang menggunaan Lima Indikator Keterampilan Berpikir Kreatif - Intan, Intan Kunanti; Fitri, Rahmadhani (Al-Alam: Islamic Science Education Journal, 2025)
Creative thinking skills are important to develop so that students are able to meet the demands of today's learning. In Biology, this ability is needed to understand problems, generate ideas, and find solutions independently. This study aims to describe the level of creative thinking skills of grade XI Fase F Bio F SMAN 2 Padang students based on five indicators, namely fluency, flexibility, originality, elaboration, and curiosity. The study used a quantitative descriptive method with an essay test as the main instrument. The results of the analysis showed that the creative thinking skills of students were not yet evenly distributed and some indicators were still in the low category. These findings emphasize the need for learning that encourages exploration, courage to express opinions, and idea development. Overall, students' creative thinking skills still need to be strengthened through learning activities that stimulate higher-level thinking processes.